Pendidikan Agama Kristen sebagai Sarana Pembentukan Pemimpin Pelayan (Servant Leader) - Benyamin Haninuna; Paskalis Haluk; Stevan Andy Pinoa; Angri Meliani Puspita Souk; Semuel Buntula'bi' (HARVESTER: Jurnal Teologi dan Kepemimpinan Kristen, 2025)
This study aims to examine the role of Christian Religious Education (CRE) as a strategic medium in shaping the character of servant leadership among students. In the context of globalization marked by leadership crises, individualism, and power-oriented practices, there is an urgent need for a leadership model grounded in Christian values, namely leadership through service. This research employs a Systematic Literature Review (SLR) by analyzing reputable academic sources that discuss the integration of CRE, servant leadership values, the role of teachers, curriculum, and faith communities. The findings reveal that CRE significantly contributes to shaping servant leaders through three main dimensions: (1) curriculum integration with Christian values such as love, humility, and service; (2) the role of teachers as life models who internalize and embody servant leadership in the teaching–learning process; and (3) the contribution of faith communities as praxis spaces where students experience and practice the values of service in real-life contexts. The study further highlights that synergy among schools, teachers, families, and faith communities creates a holistic educational ecosystem that nurtures a new generation of leaders with integrity and a service orientation. Thus, CRE functions not merely as an instrument of cognitive instruction but as a transformative means for spiritual growth and the development of leadership character aligned with the example of Jesus Christ. These findings are expected to enrich academic discourse while providing practical direction for curriculum development, pedagogical strategies, and the engagement of faith communities in forming future leaders who serve. AbstrakPenelitian ini bertujuan untuk mengkaji peran Pendidikan Agama Kristen (PAK) sebagai sarana strategis dalam membentuk karakter kepemimpinan pelayan (servant leadership) pada peserta didik. Dalam konteks globalisasi yang ditandai dengan krisis kepemimpinan, individualisme, dan orientasi kekuasaan, dibutuhkan model kepemimpinan yang berakar pada nilai-nilai Kristiani, yaitu kepemimpinan yang melayani. Pendekatan penelitian ini menggunakan Systematic Literature Review (SLR) dengan menelaah berbagai sumber akademik bereputasi yang membahas integrasi PAK, nilai kepemimpinan pelayan, peran guru, kurikulum, dan komunitas iman. Hasil kajian menunjukkan bahwa PAK memiliki kontribusi signifikan dalam membentuk pemimpin pelayan melalui tiga dimensi utama, yaitu integrasi kurikulum dengan nilai-nilai Kristiani seperti kasih, kerendahan hati, dan pelayanan; peran guru sebagai teladan hidup yang menginternalisasikan nilai kepemimpinan pelayan dalam proses belajar-mengajar; dan kontribusi komunitas iman sebagai ruang praksis bagi siswa untuk menghidupi dan mempraktikkan nilai pelayanan dalam kehidupan nyata. Penelitian ini juga menemukan bahwa sinergi antara sekolah, guru, keluarga, dan komunitas iman menciptakan ekosistem pendidikan yang holistik dalam membentuk generasi pemimpin pelayan yang berintegritas dan berorientasi pada pelayanan. Dengan demikian, PAK tidak hanya berfungsi sebagai instrumen pengajaran kognitif, tetapi juga sebagai sarana transformasi spiritual dan karakter kepemimpinan yang sejalan dengan teladan Yesus Kristus. Temuan ini diharapkan memperkaya wacana akademik sekaligus memberikan arah praktis bagi pengembangan kurikulum, strategi pembelajaran, dan keterlibatan komunitas iman dalam pembentukan pemimpin masa depan yang melayani.